ANALYSIS OF AUXETIC STRUCTURE AS IMPACT ENERGY ABSORBER AGAINST SIDE IMPACT ON ELECTRIC VEHICLE - Naufal Abdillah M, Salman
As the popularity and demand of electric vehicles keep soaring over the years, it is predicted that the annual sales of electric vehicles will reach up to 5 million by 2030. One critical component required by an electric vehicle is the battery pack consisting of multiple groups of battery cells that provides power for the functioning of the vehicle as a whole, which requires sure protection from various potential problems. The deformation of the batteries could spark a fire or explosion that in turn could endanger the passenger and surrounding presence. This leads to the extensive research on crashworthy design of protection components and its evaluation to ensure the safety of electric vehicles. This final project focuses on the analysis of the crashworthiness performance of the impact energy absorber (IEA) under side pole impact to protect the battery pack. For that purpose, auxetic structure is proposed with a special feature of having negative Poisson’s ratio, in hope to maximize the impact absorption under side pole impact loading. The methodology carried out to support this project involves CAD Design of the auxetic IEA structure using SolidWorks, simulation of a quasi-static compression model using Abaqus to validate the model and configuration, explicit dynamic simulation of the IEA-R using Abaqus, and evaluation of the result based on its specific energy absorption (SEA) value, as well as the parameter of stress and reaction force. The simulation of this study evaluates the auxetic structure as an IEA to have an advantage in the dampening of the recorded stress of up to 30% and reaction force up to 25% on relevant areas of the component in comparison to some conventional structures, with a decrease of 45% in stress and 60% of reaction force than an empty door-sill with similar mass. The result conclusively evaluates the effectiveness of the auxetic structure in comparison to the honeycomb and a square structure, and its significance in the implementation inside a door-sill that reduces stress at the surface of battery pack, as well as impact force.